2011
DOI: 10.1093/ejo/cjr009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxicity and degree of conversion of glass ionomer cements reinforced with resin

Abstract: The objective of the present study was to evaluate the cytotoxicity and degree of monomer conversion of resin-reinforced glass ionomer cements (RGIC) over different time periods. Four RGICs: Fuji Ortho LC (FOLC), Fuji Ortho Band (FOB), Orthoglass (OGL), and Multicure Glass Ionomer (MCI) were evaluated for cytotoxicity in fibroblastic L929 cells and for their degree of monomer conversion over different time periods. Three control groups were also analysed: positive control (C+), consisting of Tween 80 cell dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…1,4 Organic acids from the polyacrylic acid chains react with the glass powder, breaking the Al-O-Si bonds, and releasing aluminum and calcium ions in an aqueous medium. 1,4 Some studies [5][6][7] have demonstrated that the cytotoxic effects of GICs may be attributed to the metal components released, such as aluminum and iron. [8][9] Data obtained in studies of odontoblastic cell lineages report the solubility of these experimental materials and their possible toxic declaration of interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Organic acids from the polyacrylic acid chains react with the glass powder, breaking the Al-O-Si bonds, and releasing aluminum and calcium ions in an aqueous medium. 1,4 Some studies [5][6][7] have demonstrated that the cytotoxic effects of GICs may be attributed to the metal components released, such as aluminum and iron. [8][9] Data obtained in studies of odontoblastic cell lineages report the solubility of these experimental materials and their possible toxic declaration of interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, as far as the cytotoxicity test is concerned, the cell culture model used was in monolayer (18)(19)(20). This model was used together with the dye-uptake technique (19) because the cytotoxicity of materials can be determined by spectrophotometry (20).…”
Section: Discussionmentioning
confidence: 99%
“…Both sides of the acrylic specimens were previously sterilized with ultraviolet light (Labconco, Kansas City, MO, USA) for 30 min (18). To verify the cell response to extreme situations, other three groups were included in the study: Group CC (cell control), consisting of cells not exposed to any material; Group C+ (positive control), consisting of Tween 80 and Group C-(negative control), consisting of PBS solution in contact with the cells.…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…Spectrophotometric essay allows rapid and reliable evidence of cell viability to be obtained based on the use of vital stain incorporated by viable cells [23][24][25][26] . In this study, neutral red dye was used, as it is widely used for identifying L-929 cell viability 23,[25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, neutral red dye was used, as it is widely used for identifying L-929 cell viability 23,[25][26] . Dead or damaged cells cannot incorporate vital stain, and are thus not recognized on optical reading.…”
Section: Discussionmentioning
confidence: 99%